Experimental study of the effect of inclination angle variations of the turbine shaft on the Archimedes screw turbine efficiency - Anwar, Zainuri; Dzaky, Muhammad Irfan; Rifa'i, Ahmad Imam; Hidayati, Baiti; Sunarso, Edi (Universitas Muhammadiyah Metro, 2024)
Archimedes Screw turbine is a type of turbine that can operate at low heads. One of the parameters that influences turbine performance is the tilt angle of the turbine shaft. This research aims to determine the effect of the turbine shaft tilt angle on the performance of the Archimedes screw turbine using experimental methods. The experiment was carried out in the river of Pematang Gajah Village, Jambi Province, by varying the tilt angle of the turbine shaft, namely 10°, 20°, 30°, 40°, and 50°. The test results showed that the highest turbine efficiency occurred at a turbine tilt angle of 30° with an average efficiency value reaching 78%. This condition occurs because the flow through the turbine blade is less compared to other turbine shaft tilt conditions so that the fluid force is completely converted into energy. The electrical energy produced by turbine generators can reduce dependence on electricity supplies from the central grid and become more energy-independent. In addition, stable and affordable energy sources can improve the quality of life and support the social and economic development of society.